Multiple ubiquitin E3 ligase genes antagonistically regulate chloroplast-associated protein degradation - Mohd. Ali, S; Li, N; Soufi, Z; Yao, J; Johnson, E; Ling, Q; Jarvis, R (Cell Press, 2023)
The chloroplast is the most prominent member of a diverse group of plant organelles called the plastids, and it is characterized by its vital role in photosynthesis.1,2,3 Most of the ∼3,000 different proteins in chloroplasts are synthesized in the cytosol in precursor (preprotein) form, each with a cleavable transit peptide.4,5,6,7,8 Preproteins are imported via translocons in the outer and inner envelope membranes of the chloroplast, termed TOC and TIC, respectively.9,10,11,12,13 Discovery of the chloroplast-localized ubiquitin E3 ligase SUPPRESSOR OF PPI1 LOCUS1 (SP1) demonstrated that the nucleocytosolic ubiquitin-proteasome system (UPS) targets the TOC apparatus to dynamically control protein import and chloroplast biogenesis in response to developmental and environmental cues. The relevant UPS pathway is termed chloroplast-associated protein degradation (CHLORAD).14,15,16 Two homologs of SP1 exist, SP1-like1 (SPL1) and SPL2, but their roles have remained obscure. Here, we show that SP1 is ubiquitous in the Viridiplantae and that SPL2 and SPL1 appeared early during the evolution of the Viridiplantae and land plants, respectively. Through genetic and biochemical analysis, we reveal that SPL1 functions as a negative regulator of SP1, potentially by interfering with its ability to catalyze ubiquitination. In contrast, SPL2, the more distantly related SP1 homolog, displays partial functional redundancy with SP1. Both SPL1 and SPL2 modify the extent of leaf senescence, like SP1, but do so in diametrically opposite ways. Thus, SPL1 and SPL2 are bona fide CHLORAD system components with negative and positive regulatory functions that allow for nuanced control of this vital proteolytic pathway.